PENGARUH UKURAN PEMOTONGAN DAN PERENDAMAN LARUTAN Rhyzopus sp TERHADAP KANDUNGAN TANIN SERAT KASAR SERTA PROTEIN KASAR KULIT PISANG TANDUK (Musa acuminate Var. Typica): The Effect of the Measure of Cutting and Inclusion Solution Rhyzopus sp, on the Content of Tanin in Crude Fiber and Crude Protein of The Skin Banana Horn (Musa acuminate Var.Typica) - Hasnuni Hasnuni; nancy Lahay; Muhammad Fadlirrahman Latief (Departemen Nutrisi dan Makanan Ternak, Fakultas Peternakan, Universitas Hasanuddin, 2022)
One of the banana peel wastes that can be used as an alternative feed is the banana peel (Musa acuminata Var. Typica). This study aims to determine the effect of cutting size and immersion of Rhizopus sp on the content of tannin, crude fiber and crude protein of the skin of a banana (Musa acuminata Var. Typica). The study was conducted using a completely randomized design (CRD) with a factorial pattern in the form of cutting size and immersion time of Rhyzopus sp and anova analysis using Duncan's variance further test. The results showed that the cutting size and soaking time of Rhyzopus sp had a significant effect (P<0.01) on the value of tannins with the lowest decrease in tannin levels at the cutting size of 10 cm, soaking time of 36 hours was 0.80 ± 0.03. Cutting size and immersion time of Rhyzopus sp had a significant effect (P<0.01) on the value of crude fiber with the lowest decrease in crude fiber at a cutting size of 5 cm, soaking time for 12 hours was 8.28±0.00. Cutting size and immersion time of Rhyzopus sp had a significant effect (P<0.01) on crude protein value with the highest increase in cutting size of 5 cm, soaking time for 36 hours of 8.27±0.18. It can be concluded that the size of the cuts and the duration of immersion in the Rhyzopus sp solution can reduce the value of the content of tannins, crude fiber and increase crude protein.